PEMBERDAYAAN KELUARGA MELALUI PENYULUHAN KESEHATAN UNTUK MENINGKATKAN PENGETAHUAN DAN SIKAP DALAM PENCEGAHAN PENYAKIT CACINGAN PADA ANAK: STUDI KASUS - Siti Utami Dewi; Nida An Khofiyya (Melati Institute, 2023)
Worms’ diseases caused by worms’ infection in the human body that are transmitted through the soil and multiply so they can cause bloating, diarrhea, anemia, malnutrition, get sick easily, weak, reduce learning abilities and bothering children's growth. One of the efforts we can do to reduce the incidence of intestinal worms is doing health education. The purpose of this case study is to get an overview of the implementation of health education to increase knowledge and attitudes of families in preventing intestinal worms in children. This research design uses a descriptive method in the form of a case study with a family nursing care approach. The results of the case study showed an increase of knowledge 88.8% and attitudes 53.2% in the subject after health education was carried out. The conclusion of this case study shows that health education can increase family knowledge and attitudes in preventing intestinal worms in children. Suggestions recommended for families are to maintain personal and environmental hygiene, do a medical checkup periodic to health facilities to prevent worms’ infection.